FENOMENA EKONOMI DAN PERDAGANGAN INDONESIA DI MASA PANDEMI CORONA VIRUS DISEASE-19 (COVID-19) - Sari, Deanita (JURNAL AKUNTANSI DAN INVESTASI, 2020)
In Indonesia, based on epidemiological, resource, economic, social and cultural, security, and the magnitudo of the threat of effectiveness. President Joko Widodo began to assign PSBB which were considered to cause economic and trade problems. Based on the above problems, the writer will look at the economic and trade phenomena of Indonesia during the covid-19 pandemic. This research is a qualitative research using the phenomenological method by looking at economic and trade phenomena. This study uses secondary data by viewing statistical viddata uploaded on the web page (www.bps.go.id)Based on the research results of economic and trade phenomena, especially in the fields of Exports, Producer Prices, Wholesale Trade Prices, Inflation, Tourism, Gross Domestic Product and Labor Wages as a whole experienced weakening during the covid-19 pandemic.